Perbedaan Self-Efficacy Ditinjau dari Jenis Kelamin Siswa SMPN 174 Jakarta - Fadhilah Dwi Setyorini; Fatma Nofriza (Journal on Education, 2024)
Self-efficacy is a crucial concept related to individual's belief in their ability to execute specific actions or tasks. Research indicates that various factors influence self-efficacy, including gender. The purpose of this study is to explore the differen in self-efficacy between male and female students at SMPN 174 Jakarta. This study uses a quantitative approach with a population of 251 students in grade VIII. There is a sample of 111 students, consisting of 53 men and 58 women,, were randomly selected without regard to their class. Data were collected using a self-efficacy instrument evaluated with a Likert scale. The results revealed notable variations in self-efficacy between female and male students, with an average score of 57.36 for female students and 59.72 for male students.